Pulse Polio Immunization Coverage Evaluation In A Rural Area Of Agra District - Nandan Deoki; Mishra S K; Gupta Gajendra K; Gupta Sanjay; Maheshwari B B (Wolters Kluwer Medknow Publications, 1996)
Research Question: What is the extent of PPI Coverage and what is the source of information and motivation to the community. Objective: To assess the extent of coverage of immunization carried out during pulse polio Immunization (1995-96) in rural areas of Agra District. Study Design: Cross-sectional Setting: Selected Villages of PHC Bichpuri, covered by ICDS, in Agra District Participants: Persons who took the <3 children for immunization Sample Size: 581 Persons from 987 households Study Variables: Doses of OPV received, source of information, location of immunization site, distance traveled and mode of transport. Results: The reported achievement for the first dose was 86.6% and for the second it was 87.6%. It was found that most important sources of knowledge were Anganwadi Worker (43.54%) followed by ANM (26.88%). Majority of the immunization booths (67.29%) were working in sunshine. More than 90% villagers reached the site walking on foot. Recommendations: Efforts should be made by the worker (HW and AWW) to motivate the population for 100% coverage under the coming PPI programme. Information should be given to the worker regarding correct location of immunization site.